Talents in the Brazilian Public Sector: the Result of an Innovative Collaboration between Civil Society and the State - Toyota, Joice (Revista del CLAD Reforma y Democracia, 2019)
Certain shifts in demography, social values, and the labor market are part of a generational transformation that favors the attraction of young talents for the Brazilian public sector. However, the Brazilian State faces structural obstacles to take advantage of the opportunity to train a new generation of public professionals, among which are the poor organization and inconsistent of the Brazilian bureaucracy, its fragility as employer, and its obsolete recruitment and development methods. In this context, the civil society organization Vetor Brasil assumed the responsibility of contributing to overcome these obstacles. It launched the Public Management Trainee Program in 2015 in order to provide assistance in recruiting, selecting, and developing talented youth for public service careers. Using a method based on skills, it has received 60,000 applications and placed 280 professionals in local government positions of all Brazilian federal units. It now boasts a network of committed and diverse professionals capable of driving cultural changes in the public sector multiplying Vetor’s mission. The initiative also works as laboratory for new human resources management practices that can be tested and generate evidence. After three years of operation, the program have opened countless horizons and Vector has privileged its voice in the growing debate on the modernization of Brazil’s public sector. Trusting that the lessons learned could provide an inspiration and example for the development a growing ecosystem of civil society organizations devoted in promoting innovation within State, Vetor shares its experience in this article.
Keywords: Civil Service Reform; Personnel Selection; Competence; Administrative Innovation; State-Society Relationship; Youth; Case Analysis; Brazil